2011
DOI: 10.17146/aij.2010.25
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Gamma Irradiation on the Growth and Propagation of <em>In-Vitro</em> Chrysanthemum Shoot Explants (cv. <em>Yellow Puma</em>)

Abstract: The study on the effect of gamma irradiation on in-vitro shoot growth of chrysanthemum cv. Yellow Puma has been carried out. The aim of the study was to observe genetic variability of shoot growth caused by gamma irradiation. Shoot explants with four leaves were irradiated by gamma with dose of 10, 15 and 20 Gy with 3 replications at each of dose. The irradiated shoot explants were then transferred into fresh MS solid medium and placed in a growth room. Observation was performed on number of leaves and branche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Gamma irradiation inhibited in vitro shoot elongation of patchouli. Effect of gamma irradiation on inhibition of shoot length was observed in Triticum aestivum L. [29] Cicer [30], Corn [31], and Chrysanthemum [32]. Gamma irradiation prevented the shoot elongation of Cicer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gamma irradiation inhibited in vitro shoot elongation of patchouli. Effect of gamma irradiation on inhibition of shoot length was observed in Triticum aestivum L. [29] Cicer [30], Corn [31], and Chrysanthemum [32]. Gamma irradiation prevented the shoot elongation of Cicer.…”
Section: Resultsmentioning
confidence: 99%
“…The higher irradiation, shoot length was more affected [30]. Previous research found that gamma irradiation decreased the number of leaves and branches on Chrysanthemum [32]. Gamma-ray irradiation also had a significant impact on the shoot length of Triticum aestivum L. The shoot length decreased by 46% as the gamma dose increased [29].…”
Section: Resultsmentioning
confidence: 99%
“…Increasing demand for the new form of chrysanthemum leads to research for obtaining new varieties. Mutation breeding by radiation, a farming appliance of nuclear technology, and has been widely exploited to develop welladapted plant varieties by one or a few important qualities (Kumar et al 2006, Jain and Spencer (2006, Dwimahyani and Widiarsih 2010) Commercially important traits in horticulture plants have been altered positively by the various physical mutagens. Gamma rays are widely used among the physical mutagens for inducing mutations in owering plants due to their easy application and high e ciency.…”
Section: Introductionmentioning
confidence: 99%
“…To create novel Chrysanthemum ower color/shape mutants, radiation has been used successfully (Misra et al 2003;Dwimahyani and Widiarsih 2011). As a result, radiation-induced mutagenesis has become a critical approach for ower breeding.…”
Section: Introductionmentioning
confidence: 99%